PEMANFAATAN E-LEARNING SEBAGAI SARANA PENDUKUNG TRYOUT UJIAN AKHIR PADA SMK MULTIMEDIA TUMPANG - Suharso, Wildan; Syaifuddin, Syaifuddin; Fitriah, Lailatul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2019)
National Exams at the High School level are conducted online using computers so that all High Schools are required to be ready in terms of devices or resources, as well as the Multimedia Tumpang Vocational High School which is now ready with a number of moodle-based computers and systems that are only used consecutively. The conditions faced makes it difficult for students to get perfect scores so that a learning system that is in accordance with Government standards in the National exams is needed. Some things that make it difficult for students to get perfect scores are limited numbers of computers, limited use of e-learning, habits of students to do exam questions manually, not accustomed to applications used for examinations, the absence of e-learning systems that can be accessed in an together in large numbers, the system can be used interchangeably. Problem solving is done systematically including analyzing the conditions of the hardware they have, analyzing the conditions of the software used to support learning, building e-learning according to needs, e-learning installation so that it can be used by teachers and students as needed , training in e-learning use and management, tryout trials using e-learning, evaluating the use and management of e-learning. The final result obtained is that all students and teachers can use and utilize e-learning.